O palavrão em filmes brasileiros contemporâneos : um enfoque Bakhtiniano - Caetano, Veridiana (2015)
This study aims at introducing theoretical-methodological remarks to analyze swearwords in the contemporary Brazilian movie industry. Its general objective is to analyze swearwords which come up in two Brazilian movies by observing dialogic relations that emerge from these ideological signs. Its specific objectives are the following: (i) to analyze different intonations which emerge from the swearwords under investigation in the selected movie scenes and to understand how senses are constructed in movies; (ii) to examine the scenes in which the swearword is being said by observing the movement of the centripetal and centrifugal forces at work in the discourse; and (iii) to study aspects related to the discursive memory of these words by observing new senses that may be attributed to the swearword. Bakhtinian theoretical presuppositions (BAKHTIN, 1998, 2003, 2008a, 2008b; BAKHTIN/VOLOCHÍNOV, 2006; VOLOCHÍNOV/BAKHTIN, 2011) were employed since they keep a dialogue with studies of the movie industry (LIPOVETSKY and SERROY, 2009; STAM 1992, 2008, 2010). In order to reach those objectives, two Brazilian movies were selected: Tropa de Elite- Missão Dada é Missão Cumprida (2007) and Mato Sem Cachorro (2013). Six scenes of each movie, in which swearwords are emphasized, were analyzed. This study advocates that a swearword, like any other word, is a pluri-accented ideological sign, rather than a neutral unity. Therefore, this study argues that what differentiates swearwords, in the way they are shown in the contemporary Brazilian movies under analysis, seems to be the constitution of a tense zone whose dynamics moves between what is forbiddenand what can set people free.